Molecular and morphological evidences of Sabulina nerimanae sp. nov. (Caryophyllaceae) - Koç, Murat; Hamzaoğlu, Ergi̇n; Aksoy, Ahmet (Phytotaxa, 2021)
Strange samples of Sabulina found in the ISTO herbarium were recollected  and then compared with herbarium material of related species. It was determined that the most similar species was Sabulina gracilis. Both were compared with molecular and morphological methods. As a result, it was decided that the interesting specimens represented a new species. The new species,  Sabulina nerimanae Koç & Hamzaoğlu, is described and illustrated here and information on , distribution, habitat, micromorphological seed characters, threatened categories, and phylogenetic relationships between closely related species are given.